2021
DOI: 10.1111/aor.13945
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic mechanical circulatory support for protected ventricular tachycardia ablation: A meta‐analysis of the literature

Abstract: Acute hemodynamic decompensation (AHD) during ventricular tachycardia (VT) ablation occurs in about 11% of cases. Prophylactic use of temporary mechanical circulatory support (pro‐tMCS) has been applied to prevent AHD during VT ablation, but evidence supporting this practice is still lacking. This systematic review and meta‐analysis assessed the procedural characteristics and outcomes of pro‐tMCS for VT ablation. PubMed/Medline was screened until February 2020. Articles including adults receiving pro‐tMCS for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 41 publications
(214 reference statements)
0
15
0
Order By: Relevance
“…Finally, with respect to life-threatening arrhythmias such as ventricular tachycardia (VT), TandemHeart is the second most used pVAD after the Impella device in protected VT ablation [ 71 ]. Advantages of pVADs’ implantation include the maintenance of end-organ perfusion during VT for longer periods, which require fewer terminations of VT (anti-tachycardia pacing), thus increasing the likelihood that VT ends during ablation [ 25 ].…”
Section: Cardioprotective Devices That Unload the Heartmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, with respect to life-threatening arrhythmias such as ventricular tachycardia (VT), TandemHeart is the second most used pVAD after the Impella device in protected VT ablation [ 71 ]. Advantages of pVADs’ implantation include the maintenance of end-organ perfusion during VT for longer periods, which require fewer terminations of VT (anti-tachycardia pacing), thus increasing the likelihood that VT ends during ablation [ 25 ].…”
Section: Cardioprotective Devices That Unload the Heartmentioning
confidence: 99%
“…Advantages of pVADs’ implantation include the maintenance of end-organ perfusion during VT for longer periods, which require fewer terminations of VT (anti-tachycardia pacing), thus increasing the likelihood that VT ends during ablation [ 25 ]. Although these advantages have not been shown to prevent VT recurrence, in-hospital/30-day mortality or procedural success compared to control patients suggested that patients receiving pVADs during protected ablation might experience a reduced risk of long-term mortality [ 71 , 72 ]. Studies also demonstrate that preemptive implantation of Impella or TandemHeart in patients with systolic heart failure can prolong the time on VTs and induce a greater number of VTs [ 71 , 72 ].…”
Section: Cardioprotective Devices That Unload the Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…Impella devices have also been utilized to prophylactically prevent hemodynamic decompensation during high-risk electrophysiologic procedures, most frequently during ventricular tachycardia (VT) ablations. 9 A secondary benefit of this approach is enabling more prolonged time in VT and induction of more VT in patients with low ejection fraction. While Impella 2.5 and CP are most frequently utilized for these cases, use of the Impella 5.0 and 5.5 for protected ablations has also been described.…”
Section: Consider the Indications And Post-support Destinationsmentioning
confidence: 99%
“…(3) It is not clear if use of pVAD was performed preemptively or as a rescue. This is important because emergent use of pVAD has been shown to be associated with worse outcomes [5,8,9]. (4) The authors mention that the most prevalent cause of death was progressive shock or refractory HF.…”
Section: Commentarymentioning
confidence: 99%